Legal Responsibility of Medical Specialist for Illness or Death: The Essence of Justice - Prasetyo Edi; Andri Winjaya Laksana (Jurnal Hukum, 2026)
This study examines the legal liability of medical specialists who perform medical procedures beyond their scope of competence, resulting in patient morbidity or mortality. The issues analyzed include the essence of justice in the regulation of physician legal liability and the ideal formulation of legal policies in medical practice, particularly amidst the advancement of medical techniques. The research method employed is legal research using a socio-legal approach and explanatory specification. Data sources comprise primary and secondary legal materials, as well as empirical data in the form of complaints and decisions from the Indonesian Medical Discipline Honorary Council (MKDKI) that have attained legal finality, analyzed through descriptive qualitative methods. The results indicate that justice in physician legal liability must be understood as proportional justice, given the disparity in knowledge and authority within the therapeutic relationship between doctor and patient. Medical specialists may be held legally liable if proven to have committed competence violations, such as practicing beyond their authority, failing to refer patients, or providing inadequate medical care. This study emphasizes that physician legal liability is not solely based on the outcome, but rather on violations of professional standards, discipline, and the degree of negligence involved. Consequently, it is necessary to strengthen regulations and oversight mechanisms in medical practice to ensure patient safety and legal certainty for medical personnel.